Gestão ambiental e práticas de responsabilidade socioambiental em indústrias de Nossa Senhora do Socorro-SE - Rodrigues, Amanda da Conceição (2021)
Faced with advances in technology, the demand for industrial production has contributed to the environmental crisis that plagues planet Earth and has brought with it the need for accountability for the damage that business activities cause to the environment. This accountability is being increasingly demanded by society, communities and the government, through public policies. Therefore, environmental management strategies help organizations to understand, organize and plan the impacts that their products and services cause to the environment. Linked to this, socio-environmental responsibility is a set of ethical principles and practices that create possibilities for environmental protection in the face of anthropic action. These practices must be aligned with the goals of the 9th Sustainable Development Goal (SDG), regarding the strengthening of a culture of responsible and sustainable production and consumption. Thus, the general objective of this research was to analyze environmental management through socio-environmental responsibility actions of industries in the Industrial District of Nossa Senhora do Socorro-SE, in view of their business values and alignment with the 9th SDG. The study was justified by the current awareness of the industrial sector regarding the socio-environmental impacts caused by its activities; the socioenvironmental guidelines of the Urban Development Master Plan for the municipality of Nossa Senhora do Socorro-SE; and by the considerable growth of the Industrial District of the municipality. The study was based on topics such as progress and its impacts, covering socioenvironmental ethics, corporate social and environmental responsibility, sustainable development and the SDGs, in addition to corporate environmental management. The research methodology perfected the inductive method; of an applied nature; qualitativequantitative approach; field research with the application of semi-structured and remote interviews (given the health restrictions of the COVID-19 pandemic) with 9 (nine) companies in the Industrial District of Socorro (DIS), selected by the convenience or intentional sampling technique and by accessibility. Data treatment and analysis were performed by tabulation, coding and categorization and were represented by graphs, tables and content analysis. The main results showed that the DIS companies are aligned with SDG 9, exercising a socio-environmentally responsible posture with their employees, as well as with the surrounding ecosystem, with the community and with society; and describes the main actions of industries in the practice of socio-environmental responsibility, namely: concern with the disposal and reuse of solid waste, improvement and qualification of personnel and participation and contribution to social projects. In the final considerations, proposals for improvements were suggested, such as the indication of an action plan for socioenvironmental practices for the community, together with the Residents Association (Associação Belém), with the Association of Companies of the Industrial District of Socorro (ASSEDIS) and with the City Hall. At the end of this part, topics for future work were indicated, such as a research on strategic management in industries in the Industrial District of Nossa Senhora do Socorro.